Cost-effectiveness of exercise on prescription with telephone support among women in general practice over 2 years. Issue 15 (16th November 2010) - Elley, C Raina; Garrett, Sue; Rose, Sally B; O'Dea, Des; Lawton, Beverley A; Moyes, Simon A; Dowell, Anthony C
Abstract : Aim: To assess the cost-effectiveness of exercise on prescription with ongoing support in general practice. Methods: Prospective cost-effectiveness study undertaken as part of the 2-year Women's lifestyle study randomised controlled trial involving 1089 'less-active' women aged 40–74. The 'enhanced Green Prescription' intervention included written exercise prescription and brief advice from a primary care nurse, face-to-face follow-up at 6 months, and 9 months of telephone support. The primary outcome was incremental cost of moving one 'less-active' person into the 'active' category over 24 months. Direct costs of programme delivery were recorded. Other (indirect) costs covered in the analyses included participant costs of exercise, costs of primary and secondary healthcare utilisation, allied health therapies and time off work (lost productivity). Cost–effectiveness ratios were calculated with and without including indirect costs. Results: Follow-up rates were 93% at 12 months and 89% at 24 months. Significant improvements in physical activity were found at 12 and 24 months (p<0.01). The exercise programme cost was New Zealand dollars (NZ$) 93.68 (€45.90) per participant. There was no significant difference in indirect costs over the course of the trial between the two groups (rate ratios: 0.99 (95% CI 0.81 to 1.2) at 12 months and 1.01 (95% CI 0.83 to 1.23) at 24 months, p=0.9). Cost–effectiveness ratios using programme costs were NZ$687 (€331) per person made 'active' and sustained at 12 months and NZ$1407 (€678) per person made 'active' and sustained at 24 months. Conclusions: This nurse-delivered programme with ongoing support is very cost-effective and compares favourably with other primary care and community-based physical activity interventions internationally.